Návrh a implementace automatického obchodního systému pro devizový trh - Doležal, Radek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zaobírá problematikou návrhu a implementace automatického obchodního systému pro devizový trh. Obsahuje rozbor základních pojmů, metod technické analýzy a money managementu potřebných pro návrh strategie automatického systému. Výstupem práce je vlastní automatický obchodní systém, jehož robustnost a stabilita je otestována technikou walk forward analýzy.

The subject of this diploma thesis is a design and implementation of an automated trading system for the forex market. It includes an analysis of the main concepts and methods of technical analysis and money management, which constitute an essential theoretical basis for the subsequent practical design of an automatic system. The objective of this work is a development of an automated trading system whose robustness and stability is tested by a walk forward analysis.
Design and Implementation of Automatic Trading System for Exchange Market
Keywords: Forex; devizový trh; automatický obchodní systém; robot; měnové páry; technická analýza; technické indikátory; klouzavé průměry; RSI; ADX; MACD; money management; řízení rizik; Forex; foreign exchange market; automated trading system; robot; currency pairs; technical analysis; technical indicators; moving averages; RSI; ADX; MACD; money management; risk management